Research on the Loss of Three-level T-type Inverter in SVG - CHEN Mingfeng; LEI Wanjun; FU Chongli; WANG Yue (Kongzhi Yu Xinxi Jishu)
It introduced topology structures of three-phase three-level T-type converter in SVG and its SVPWM modulation strategy,analyzed the conduction loss and switch loss of IGBT modules of the converters in different working conditions and gave the equations of the loss. The loss conditions of IGBTs in SVG were presented in different working modes by simulation.